Bifunctional Au@Pt/Au core@shell Nanoparticles As Novel Electrocatalytic Tags in Immunosensing: Application for Alzheimer’s Disease Biomarker Detection - Iglesias-Mayor, Alba; Amor-Gutiérrez, Olaya; Novelli, Antonello; Fernández-Sánchez, María-Teresa; Costa-García, Agustín; de la Escosura-Muñiz, Alfredo (Analytical chemistry (Washington), 2020)
In this work, bifunctional core@shell Au@Pt/Au NPs are presented as novel tags for electrochemical immunosensing. Au@Pt/Au NPs were synthesized following a chemical route based on successive metal depositions and galvanic replacement reactions from the starting AuNPs. Au protuberances growth on the surface of Au@Pt NPs allowed their easy bioconjugation with antibodies, while the high catalytic Pt surface area was approached for their sensitive detection through the electrocatalyzed water oxidation reaction (WOR) at neutral pH. Moreover, the synergy between Au and Pt metals on the NP surface also lead to an increased catalytic activity, improving the sensitivity of the NP detection. Cyclic voltammetry and chronoamperometry were used for the evaluation of the Au@Pt/Au NPs electrocatalytic activity toward WOR. The chronoamperometric current recorded at a fixed potential of +1.35 V was selected as the analytical signal, allowing the quantification of Au@Pt/Au NPs at 1013 NPs/mL levels. The optimized electrocatalytic method was applied to the quantification of conformationally altered p53 peptide Alzheimer’s disease (AD) biomarker in a competitive immunoassay using magnetic bead (MB) platforms at levels as low as 66 nM. The performance of the system in a real scenario was demonstrated analyzing plasma samples from a cognitively healthy subject. This novel Au@Pt/Au NPs-based electrocatalytic immunoassay has the advantage, over common methods for NP tags electrochemical detection, of the signal generation in the same neutral medium where the immunoassay takes place (0.1 M PBS pH 7.2), avoiding the use of additional and more hazardous reagents and paving the way to future integrated biosensing systems.